2002
DOI: 10.1063/1.1506307
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of absolute rate coefficients and product branching ratios for the C(3P)+allene reaction system

Abstract: An ab initio/Rice-Ramsperger-Kassel-Marcus prediction of rate constant and product branching ratios for unimolecular decomposition of propen-2-ol and related H + CH 2 COHCH 2 reaction J. Chem. Phys. 129, 234301 (2008) Complex chemical reactions in the gas phase can be decomposed into a network of elementary ͑e.g., unimolecular and bimolecular͒ steps which may involve multiple reactant channels, multiple intermediates, and multiple products. The modeling of such reactions involves describing the molecular speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Details of the calculations are described elsewhere 38. Although a recent study 39 suggested that the neglect of angular momentum conservation may be justified in some cases, it needs to be tested for specific cases. Accordingly, angular momentum conservation was incorporated in the calculations, as some of the reactions involve the movement of the relatively heavy carbon atoms.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Details of the calculations are described elsewhere 38. Although a recent study 39 suggested that the neglect of angular momentum conservation may be justified in some cases, it needs to be tested for specific cases. Accordingly, angular momentum conservation was incorporated in the calculations, as some of the reactions involve the movement of the relatively heavy carbon atoms.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In addition to possessing little or no impeding barriers anywhere along the pathway, reactions must also be at least minimally exothermic to be relevant to gas-phase chemistry in the interstellar medium. A number of addition reactions involving radicals such as C 2 H, CN, and C and various hydrocarbons possessing double or triple bonds have been shown both experimentally and theoretically to meet these criteria. Examples of both cyclic and noncyclic hydrocarbon reactants are known.…”
Section: Introductionmentioning
confidence: 99%
“…Insertion-elimination reactions of the type C þ C n H m -C n11 H mÀ1 þ H have been invoked in the synthesis of large carbon-bearing species in ISCs. 1 Ab initio calculations have been performed on the C þ allene, 8,9 C þ propyne 8,10 and C þ propylene 11 systems, indicating that hydrogen atom production is one of the major exit channels. Additional theoretical predictions of product branching ratio have been performed on C þ allene reaction 9 using microcanonical variational transition state theory.…”
Section: Introductionmentioning
confidence: 99%
“…1 Ab initio calculations have been performed on the C þ allene, 8,9 C þ propyne 8,10 and C þ propylene 11 systems, indicating that hydrogen atom production is one of the major exit channels. Additional theoretical predictions of product branching ratio have been performed on C þ allene reaction 9 using microcanonical variational transition state theory. There are only two experimental studies on products.…”
Section: Introductionmentioning
confidence: 99%